To talk or not to talk: an analysis of parents’ intentions to talk with children about different sexual topics using the theory of planned behavior - Astle, Shelby (Kansas State University, 2020)
Although parent-child sexual communication (PCSC) positively affects the sexual outcomes of children, parents face many barriers to engaging in PCSC. Based on the Theory of Planned Behavior (TPB), this study aims to explore what factors are associated with parental intentions to talk with their children about different sexual topics. A sample of 561 parents of an oldest child between the ages of 6-11 were recruited through Prolific.com to complete a survey on this topic. Results showed that the majority of parents intend to discuss a variety of sexual topics with their children but are less likely to have intentions of discussing more sensitive topics. All components of TPB (attitudes, subjective norms, self-efficacy) were significantly associated with at least three of the five categories of sexual topics (“the basics,” “pleasure,” “sex in relationships,” “gender identity/sexual orientation,” and the “religious meaning of sex”). Of the TPB components, self-efficacy was most consistently and strongly associated with increased PCSC intentions of all topics, followed by the attitude of believing sex education was the parents’ responsibility. These findings support the assumptions of TPB as applied to PCSC. Parent education should incorporate promoting positive attitudes, subjective norms, and self-efficacy regarding PCSC in order to help parents overcome barriers to PCSC. These findings suggest that building self-efficacy and helping parents feel responsible for educating their children about sex would be most important in attempting to increase parental intentions to engage in PCSC on a wide variety of topics.
Keywords: Parent-child sexual communication; Quantitative research; Theory of Planned Behavior; Intentions; Sexuality